2023
DOI: 10.37934/araset.33.1.5366
|View full text |Cite
|
Sign up to set email alerts
|

Smart Agricultural Monitoring System using IoT Application for Chili Plants

Nurhadirah Azman,
Darmawaty Mohd Ali,
Yusmardiah Yusuf

Abstract: The use of IoT applications for agricultural in Malaysia is still low. The farmers are mainly using the traditional method compared to modern agriculture by using advanced technology system like IoT application. However, the use of traditional agriculture requires a lot of work and use of labour. This will result their agricultural system become less efficient and quality of production becoming low. Thus, development of system for monitoring and automation are needed to help farmers to manage their agriculture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The study in paper [12] using IoT to detect soil moisture and measure plant height with an addition of an automated system that can control the rate of fertilizer applied to the chili plants, as well as a water pump that supplies water to the chili plants via Remote XY Apps. Fares M. A. Taha et al, [13], in his study revealed that within the IoT technologies, farmers can monitor their greenhouse online every 24 hours, regardless of time or location.…”
Section: Related Workmentioning
confidence: 99%

IoT Based Greenhouse Condition Monitoring System for Chili Plant Growth

Muhammad Syamim Mohammad Pandi,
Roslan Seman,
Aini Hafizah Mohd Saod
et al. 2024
ARASET
“…The study in paper [12] using IoT to detect soil moisture and measure plant height with an addition of an automated system that can control the rate of fertilizer applied to the chili plants, as well as a water pump that supplies water to the chili plants via Remote XY Apps. Fares M. A. Taha et al, [13], in his study revealed that within the IoT technologies, farmers can monitor their greenhouse online every 24 hours, regardless of time or location.…”
Section: Related Workmentioning
confidence: 99%

IoT Based Greenhouse Condition Monitoring System for Chili Plant Growth

Muhammad Syamim Mohammad Pandi,
Roslan Seman,
Aini Hafizah Mohd Saod
et al. 2024
ARASET